Development and evaluation of a Nursing Assistant Computerized Education Programme. - Ersek M; Wood BB (International Journal of Palliative Nursing, 2008)
Aim: To describe the development and evaluation of the Nursing Assistant Computerized Education Programme (NA-CEP), a computer-based palliative care curriculum for nursing assistants. Methods: Sixty-five nursing assistants working in various clinical settings completed measures to evaluate usability, clarity, and relevance of the programme to their work. Participants' end-of-life knowledge and confidence also was assessed before and after NA-CEP use. Results: Findings indicate that NA-CEP is easy to use, clearly presented, appropriate in reading level and content, and highly relevant to nursing assistant practice. NA-CEP also significantly increased nursing assistants' knowledge about palliative care. Conclusions: Evaluation findings indicate that NA-CEP is a useful tool for nurses and others who are responsible for training, orientation, and continuing education of nursing assistants.